Shu-Xie decoction alleviates oxidative stress and colon injury in acute sleep-deprived mice by suppressing p62/KEAP1/NRF2/HO1/NQO1 signaling - Wang, Mengyuan; Li, Bo; Liu, Yijiang; Zhang, Mengting; Huang, Caoxin; Cai, Teng; Jia, Yibing; Huang, Xiaoqing; Ke, Hongfei; Liu, Suhuan; Yang, Shuyu (Frontiers in Pharmacology, 2023)
Introduction: Sleep disorders are common clinical psychosomatic disorders that can co-exist with a variety of conditions. In humans and animal models, sleep deprivation (SD) is closely related with gastrointestinal diseases. Shu-Xie Decoction (SX) is a traditional Chinese medicine (TCM) with anti-nociceptive, anti-inflammatory, and antidepressant properties. SX is effective in the clinic for treating patients with abnormal sleep and/or gastrointestinal disorders, but the underlying mechanisms are not known. This study investigated the mechanisms by which SX alleviates SD-induced colon injury in vivo. Methods: C57BL/6 mice were placed on an automated sleep deprivation system for 72 h to generate an acute sleep deprivation (ASD) model, and low-dose SX (SXL), high-dose SX (SXH), or S-zopiclone (S-z) as a positive control using the oral gavage were given during the whole ASD-induced period for one time each day. The colon length was measured and the colon morphology was visualized using hematoxylin and eosin (H&E) staining. ROS and the redox biomarkers include reduced glutathione (GSH), malondialdehyde (MDA), and superoxide dismutase (SOD) were detected. Quantitative real-time PCR (qRT-PCR), molecular docking, immunofluorescence and western blotting assays were performed to detect the antioxidant signaling pathways. Results: ASD significantly increased FBG levels, decreased colon length, moderately increased the infiltration of inflammatory cells in the colon mucosa, altered the colon mucosal structure, increased the levels of ROS, GSH, MDA, and SOD activity compared with the controls. These adverse effects were significantly alleviated by SX treatment. ASD induced nuclear translocation of NRF2 in the colon mucosal cells and increased the expression levels of p62, NQO1, and HO1 transcripts and proteins, but these effects were reversed by SX treatment. Conclusion: SX decoction ameliorated ASD-induced oxidative stress and colon injury by suppressing the p62/KEAP1/NRF2/HO1/NQO1 signaling pathway. In conclusion, combined clinical experience, SX may be a promising drug for sleep disorder combined with colitis.